Leprosy in the Guise of Skin Tuberculosis - Complexities of Diagnostics - V. G. Semyonova; A. E. Karamova; M. A. Nefyodova (State Scientific Center of Dermatovenereology and Cosmetology, 2018)
Objective: demonstration of the case of the leprosy late diagnosis at the female patient previously watched with the diagnosis «skin tuberculosis». Materials and Methods. A 69 years old female patient watched from 2011 to 2016 with the diagnosis «skin tuberculosis» and was cured with weak effect; in 2016 the diagnosis «skin tuberculosis» was not confirmed. She undergone assessment at the State Research Centre for Dermatovenereology and Cosmetology of the Ministry of Health of the Russian Federation. The assessment included bacterioscopy of skin scrapings, pathomorphological studies of biopsy samples, molecular genetic testing. Results. On the grounds of complaints, medical history, data of surveying and physical examination, results of the clinical-laboratory studies the following diagnosis was stated: «dimorphous leprosy, leprosy BB (multibacillary leprosy, border line leprosy, active stage). Conclusion. The present observation indicates that the variety of leprosy clinical presentations and lack of suspicions on account of this ultra-rare disease lead to late diagnosis.